The Effect of Guided Discovery Learning Model on the Science Process Skills of Students in State VII Bangil Middle School Class VII on Environmental Pollution Materials - Sabila Nurul Adilah; Nur Efendi (Proceedings of The ICECRS, 2020)
This study aims to determine the effect of Guided discovery learning models on the science process skills of students in SMP Negeri 3 Bangil class VII on the material of environmental pollution. This type of research is quasi experimental, with non equivalent design pre-test and post-test control group. The sampling technique used purposive sampling obtained 2 classes, namely class VII G as a control class and class VII H as an experimental class. The instrument of this research is a test of science process skills in environmental pollutants with data collection techniques using the test method, namely pre-test and post-test. Data analysis techniques were carried out using the t-test. The results showed that the Guided discovery learning model had a significant effect on the science process skills of students in SMP Negeri 3 Bangil class VII on the material of environmental pollution.